Verifying stereo vision using structure from motion - Van Wyk, Barry-Michael Morne (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Mathematical Sciences. Applied Mathematics))--Stellenbosch University, 2008.